A Comparison of Direct and Indirect Flexibilities on the Self-Consumption of an Office Building: The Case of Predis-MHI, a Smart Office Building - Twum-Duah, Nana Kofi; Amayri, Manar; Ploix, Stéphane; Wurtz, Frédéric (Frontiers in Energy Research, 2022)
he purpose of this paper is to provide a method for assessing the impact of direct and indirect flexibilities on the self-consumption of office buildings. The goal is to assess how both the human actors and technical interventions can affect or mitigate deviations in the self-consumption level of a building from its optimal. This paper considers the Predis-MHi platform (a living lab) as a representative case study and applies a Mixed Integer Linear Programming optimization to manage both the direct (stationary battery charging) and indirect flexibilities (Electric Vehicle charging when users plug and unplug their vehicles). Our results indicate that the potential for a building’s self-consumption improvement using indirect flexibilities does exist and can be quantified. However, this type of flexibility is highly dependent on human actors which presents a high level of uncertainty and is difficult to account for in all stages of a building’s development and use. Direct flexibilities such as stationary battery storage can be used to mitigate the undesired effects of having significant levels of indirect flexibilities on a tertiary sector building’s energy performance. The results from this study could potentially be modeled into an indicator, which would serve to influence occupant behavior towards a desired optimal.